Case Report: A left ventricular pseudoaneurysm detected by cardiac magnetic resonance more than 1 year after a percutaneous transluminal coronary intervention - Liu, Yuanyuan; Xu, Ge; Shi, Funan; Yang, Jing; Gou, Ruiqiang; Chen, Zixian; Cao, Liang (Frontiers in Cardiovascular Medicine, 2024)
Pseudoaneurysm is a rare but lethal complication of acute myocardial infarction. In this study, we present a unique case of a patient with left ventricular free wall rupture detected by cardiac magnetic resonance more than 1 year after a percutaneous transluminal coronary intervention.